1985
DOI: 10.1159/000457031
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in Offspring Associated with Prenatal Marihuana Exposure

Abstract: 5 newborn infants, whose mothers acknowledged steady use of marihuana prior to and during pregnancies, displayed symptoms of intrauterine growth retardation, neurological problems, and abnormal morphogenesis. These findings fit in with the experimental studies and surveys of pregnant human populations which have indicated that cannabis products have teratogenic potential, though rigorous proof must await further information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Additionally, animal studies have shown that marijuana exposure affects somatic and germ cells through mutations, deletions, translocations, and other aberrations (Zimmerman andZimmerman, 1990 -1991); the genetic effect of marijuana exposure on somatic cells has also been shown in humans (Ammenheuser et al, 1998). Marijuana use has been associated with low birth weight and other adverse fetal growth parameters in several human studies (Tennes et al, 1985;Hatch and Bracken, 1986;Day et al, 1991), but reported associations between marijuana and birth defects have been inconclusive (Hingson et al, 1982;Gibson et al, 1983;Qazi et al, 1985;O'Connell and Fried, 1984;Zuckerman et al, 1989;Fried, 1991;Torfs et al, 1994). A literature review did not reveal any studies that identified an association between maternal marijuana use and VSD, though the BWIS found a 50% increase in the risk of isolated membranous VSD associated with paternal marijuana use (Ewing et al, 1997).…”
Section: Marijuana Usementioning
confidence: 99%
“…Additionally, animal studies have shown that marijuana exposure affects somatic and germ cells through mutations, deletions, translocations, and other aberrations (Zimmerman andZimmerman, 1990 -1991); the genetic effect of marijuana exposure on somatic cells has also been shown in humans (Ammenheuser et al, 1998). Marijuana use has been associated with low birth weight and other adverse fetal growth parameters in several human studies (Tennes et al, 1985;Hatch and Bracken, 1986;Day et al, 1991), but reported associations between marijuana and birth defects have been inconclusive (Hingson et al, 1982;Gibson et al, 1983;Qazi et al, 1985;O'Connell and Fried, 1984;Zuckerman et al, 1989;Fried, 1991;Torfs et al, 1994). A literature review did not reveal any studies that identified an association between maternal marijuana use and VSD, though the BWIS found a 50% increase in the risk of isolated membranous VSD associated with paternal marijuana use (Ewing et al, 1997).…”
Section: Marijuana Usementioning
confidence: 99%
“…To further ascertain whether embryos deficient in CB receptors respond to endocannabinoids in vitro, two-cell wild-type or mutant embryos were cultured in the presence or absence of AEA. While a comparable development of wildtype and mutant embryos was observed in the absence of Whan et al (2006) In female fertility Induction of foetal abnormalities and early pregnancy termination Persaud and Ellington (1967) Disruption of menstrual cycle Bauman (1980) Inhibition of prolactin secretion Bauman (1980) and Mendelson et al (1985) Induction of greater difficulty at delivery Greenland et al (1982Greenland et al ( , 1983 Suppression or increase of serum LH levels in a menstrual stagespecific manner Mendelson and Mello (1984) and Mendelson et al (1986) Increase of the incidence of preterm birth Fried et al (1984), Hatch and Bracken (1986), Day et al (1991) and Sherwood et al (1999) Induction of intrauterine foetal growth restriction Qazi et al (1985), Frank et al (1990) Induction of poor oocyte retrieval rate upon IVF treatment Klonoff-Cohen et al (2006) Abbreviations: IVF, in vitro fertilization; LH, luteinizing hormone; THC, D 9 -tetrahydrocannabinol.…”
Section: Type-2 Cannabinoid Receptors In Female Fertility: Animal Stumentioning
confidence: 99%
“…There are, however, two reports of anomalies which were interpreted as being linked to prenatal marihuana use. One is a large study (Hingson et al., 1982) and the other involves a report on five individuals (Qazi, Mariano, Bellar, Milman, & Crumbleholme, 1985). In both cases, the anomalies noted are part of the diagnostic criteria for the FAS and the findings may reflect a lack of control for confounding factors and/or the relative risk status of the women in the studies.…”
Section: Behavioral Teratologic Consequences Of Prenatal Exposure To mentioning
confidence: 99%